Morquio Syndrome in Two Siblings: A Case Report - Malla, KK; Malla, T; Basnet, S; Rao, KS; Tiwari, PK; Ghosh, A; KC, N (Journal of Nepal Paediatric Society, 2011)
Morquio syndrome is a rare inherited autosomal recessive disorder characterized by the accumulation of mucopolysaccharides (glycosaminoglycans) in various body tissues. It is rare cause of dwarfism. Many pediatricians therefore are unlikely to see this case hence may miss the diagnosis due to lack of experience. With this view we report two siblings with this dwarfism highlighting the classical clinical and radiological presentation. Key words: Mucopolysaccharidosis; Morquio syndrome DOI: 10.3126/jnps.v31i1.3541 J Nep Paedtr Soc 2010;31(1):68-71